THE IMPROVING STUDENTS’ PRONUNCIATION ABILITY BY USING ELSA SPEAK AS MEDIA IN XI AKUNTANSI 1 CLASS OF SMK NEGERI 1 KUTACANE ACADEMIC YEAR 2022/2023 - Andika Surya Pratama; Wikiaprian Pinim; Abdul Halim (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
Most of the schools in indonesia focus on teaching translation and grammar without providing a lot of chances for students to practice their pronunciation skill in the classroom activities. The teachers just translate what they read on the book. The purpose of this research is to see Whether ELSA Speak Application can improve students' pronunciation ability or not. This research applies the experiment design. And The design that is used in this study is one group pre-test and post-test design to masured students’ pronunciation ability. Population of this research in XI Akuntansi 1 is 324 Students and took sample as much 36 students. This research also uses quantitative method to analyse the data. The data of pre- test and post-test of this research showed any improvement and calculated by using t-test, it was founded that tobservation = 15,41 and ttable of level α 5% with df n – 1 (36 – 1 = 35) = 2,030. That means the hyphotesis of this research is received because tobservation higher than ttable 15,41 > 2,030. Based on the findings, researcher found that ELSA Speak Application can improve students’ pronunciation ability at SMK Negeri 1 Kutacane especially XI Akuntansi 1 Class. This ELSA Speaking Application showed improvement for the students’ pronunciation ability was measured by the score of the pre-test and post-test. And it was proven by because tobservation is higher than t -table..